Study of the effect of interleukin-6 gene polymorphism in patients with rheumatoid arthritis - Marwa H Sedira; Omneia A Seoudy; Laila A Ahmed; Shahinaz El Attar; Eman F Mohamed (Wolters Kluwer Medknow Publications, 2019)
Background Rheumatoid arthritis (RA) is an autoimmune disease that results in a chronic, systemic inflammatory disorder that may affect many tissues and organs, but principally attacks synovial joints. Although the clear etiology of RA remains to be elucidated, it is widely accepted that RA is a complex disease, and both environmental and genetic factors can contribute to disease initiation as well as its evolution. The −174G/C polymorphism of interleukin-6 (IL-6) gene has been reported to be responsible for changes in the expression of IL-6, which could in turn lead to greater inflammation and thus affect the clinical status of patients with RA. Aim To determine the association of IL-6 gene polymorphism with patients with RA by studying the frequency of the polymorphism of IL-6 (−174G/C) gene in those patients compared with healthy participants to predict the risk of development of RA. Patients and methods The study was conducted on 200 (150 patients with RA and 50 age-matched and sex-matched healthy control) adult Egyptian patients. IL-6 (−174G/C) genotypes were determined by PCR-restriction fragment length polymorphism analysis. Results The prevalence of polymorphic genotype of GC and CC and C allele was statistically significantly increased in patients with RA than in control (P<0.001). Conclusion The GC and CC genotype and C allele of IL-6 (−174G/C) may represent a significant genetic molecular marker to predict the risk of RA.